Macrozoobenthos Abundance in Summer Beach Muara Badak, Kutai Kartanegara Regency - Midlan Witrawan; Irma Suryana; Irwan Ramadhan Ritonga (Sam Ratulangi University, Manado, Indonesia, 2026)
Macrozoobenthos serves as a sensitive bioindicator for changes in aquatic environmental conditions, particularly in coastal areas vulnerable to anthropogenic pressures. This study aims to identify species composition and analyze the abundance of macrozoobenthos in the Summer Beach area, Muara Badak, Kutai Kartanegara Regency. Sampling was conducted from January to April 2024 at three stations using the line transect and quadrat plot method. The results identified 14 macrozoobenthos species belonging to 10 genera from the class Gastropoda (Babylonia formosae, Eunaticina albosutura, Murex tribulus, Telescopium telescopium, Indothais blanfordi, Cerithidea cingulata, Turritella terebra, Brunneifusus ternatanus, Nassarius olivaceus, Olivella biplicata) and 4 genera from the class Bivalvia (Tegillarca granosa, Geloina expansa, Heteranomia squamula, Chamelea gallina). Ecological index analysis showed moderate diversity (H’), high evenness (E), and low dominance (C) values at all stations. Correlation analysis revealed a strong relationship between phosphate concentration and macrozoobenthos abundance, while the relationship with nitrate was very weak. These findings indicate that phosphate is a key parameter influencing the macrozoobenthos community structure at the study site.